Relation between Visual Impression of Slide Fastener with Different Color Technology Method and Its Reflection Properties (Journal of Fiber Bioengineering and Informatics, 2014)
A slide fastener (i.e., zipper) is widely used as a secondary material in apparel products. However, thetexture of the slide fastener is totally different from the main fabric because the reflection propertieschange according to the structure or the material. Traditionally, the appearance of the slide fastenerhas been considered unimportant and so is often concealed. However, recently, novel color technologiessuch as structural color and mimetic metallic processing have been proposed for slide fasteners madefrom low-cost plastic. The aesthetics and modern appearance of these new slide fasteners have becomeattractive to end-users. In spite of the growth of slide fasteners with novel colors, no research hasinvestigated or assessed the applicable photometric or colorimetric methodologies. The absence of aquantitative test method decreases the efficiency of the production of slide fasteners. This study proposesa quantitative methodology to assess the aesthetics of slide fasteners produced with either conventionalor the novel color technologies, based on a data set of light reflection properties of slide fasteners. First,the structure of subjective attributes obtained from the human visual sense was analyzed by sensoryevaluation and factor analysis. Then, the measurement of the light reflection properties of slide fastenerswas conducted with an experimental goniophotometric system developed in this study. The parametersthat highly correlated with the subjective scores of representative features were explored. As a result,three principal factors, “profoundness ” , “elegance ”  and “novelty ”  were identified as aesthetic factors forslide fasteners.